2018
DOI: 10.1038/gim.2018.41
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing offers additional but limited clinical utility compared with reanalysis of whole-exome sequencing

Abstract: In this study, we showed that 30% of the positive cases identified by WGS could be identified by reanalyzing the WES raw data, and WGS achieved an only 7% higher detection rate. Therefore, until the cost of WGS approximates that of WES, reanalyzing WES raw data is recommended before performing WGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 21 publications
0
98
0
1
Order By: Relevance
“…Of note, 11 cases classified as nondiagnostic in this study were ultimately clinically diagnosed with multiple system atrophy, cerebellar type, and another case was identified with a VUS associated with increased risk for this condition (Gilman et al, 2008;Zhao et al, 2016). We also reclassified variants from our previously reported 76 cases (Fogel et al, 2014) based on current annotation, which has been shown to improve diagnosis over time (Alfares et al, 2018;Ewans et al, 2018;Fogel, 2018b This recessive disorder was diagnosed clinically due to its distinctive phenotype, a second pathogenic variant is presumed to be noncoding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of note, 11 cases classified as nondiagnostic in this study were ultimately clinically diagnosed with multiple system atrophy, cerebellar type, and another case was identified with a VUS associated with increased risk for this condition (Gilman et al, 2008;Zhao et al, 2016). We also reclassified variants from our previously reported 76 cases (Fogel et al, 2014) based on current annotation, which has been shown to improve diagnosis over time (Alfares et al, 2018;Ewans et al, 2018;Fogel, 2018b This recessive disorder was diagnosed clinically due to its distinctive phenotype, a second pathogenic variant is presumed to be noncoding.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, 11 cases classified as nondiagnostic in this study were ultimately clinically diagnosed with multiple system atrophy, cerebellar type, and another case was identified with a VUS associated with increased risk for this condition (Gilman et al, ; Zhao et al, ). We also reclassified variants from our previously reported 76 cases (Fogel et al, ) based on current annotation, which has been shown to improve diagnosis over time (Alfares et al, ; Ewans et al, ; Fogel, ; Fogel, Lee, Strom, Deignan, & Nelson, ; Fogel et al, ; Nambot et al, ; Rexach et al, ; Wright et al, ). This resulted in four cases previously classified as nondiagnostic or having a reportable VUS being reclassified with a pathogenic/likely pathogenic genetic variant.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that CES will never reach 100% diagnostic rate even in patients with a clearly genetic etiology because of technical limitations. Despite the encouraging early results from WGS in these “negative” cases, the full potential of WGS in patients who could not be diagnosed by CES remains to be seen (Alfares et al, ). Testing other tissue sources as well as additional modalities at the RNA, epigenetic, and multilocus levels will likely be necessary to resolve an even higher proportion of cases.…”
Section: Discussionmentioning
confidence: 99%
“…As the cerebellar findings were unique to WBS patient cohort and since the parents were consanguineous, we looked for the possibility of another gene to explain this radiological finding. Further review of the WES data revealed a likely pathogenic homozygous variant (NM_138395.3:c.1595C>G, p.(Ala532Gly)) in MARS2 gene (MIM# 609728), associated with cerebellar atrophy [Thiffault et al, 2006; Alfares et al, 2018]. The variant was absent from gnomAD and our internal control database but presented in his sibling who also had cerebellar atrophy on brain imaging and heterozygote for the familial DDX11 variant.…”
Section: Discussionmentioning
confidence: 99%